SMALL AND MEDIUM ENTERPRISES AS GENERATORS OF THE SUSTAINABLE REGIONAL DEVELOPMENT - Premović, Jelena; Boljević, Agneš; Arsić, LJiljana (Economics of Agriculture, 2011)
One of the basic task of the macroeconomic policy of each country is to insure the sustainable economic development. Implementation of the sustainable development requires activities on all levels - from local and regional to national authorities. In the contemporary international environment, SMEs are considered as one of the leading forces of the sustainable economic development. In the OECD countries, SMEs create 55% GDP making more than 95% of the entire business with 60-70% of the employees. Adaptibility, innovative potential and local connection are three basic characteristics of the SMEs, which making them the key factor in the process of the strategy of the sustainable local and regional economic development implementation. In order to SMEs realize the role as a local development encouragers, the adequate support of local and regional authorities is also needed.